Topology-Based and Event-Oriented Approach to Simulation of Cyber- Physical Systems - 郑君玺 张平 金培根 李方 杜广龙 (东华大学学报（英文版）, 2016)
A simulation model for cyber.physical systems （CPSs） was presented. The model was developed by the method of combination of topology-based and event-oriented that could be used to simulate systems with routing flexibility, service.selection flexibility and service- mode flexibility overall by integrating the strategies related. The validity of the model has been verified by two extensive experiments.